POLITIK IDENTITAS LOKAL DALAM PROSES DEMOKRASI INDONESIA - Yus Hermansyah (Universitas Islam Darul Ulum Lamongan, 2022)
The revival of identity politics at the local level in democracy in Indonesia goes hand in hand with the politics of decentralization. Actors and political elites use this issue to share the power cake under the pretext of justice and prosperity. This study uses a descriptive qualitative method through data collection and various literature which are then analyzed. The results of the study conclude that the factor of identity politics in democracy in Indonesia has not been touched substantially. Democracy is still stuck in procedural and ethnic identity sentiments which still lead to discriminatory practices and exclusivity for certain ethnicities.